Remodeling Microenvironment for Endogenous Repair through Precise Modulation of Chondroitin Sulfate Proteoglycans Following Spinal Cord Injury. Issue 6 (18th November 2022) - Sun, Xiumin; Liu, Haiqian; Tan, Zan; Hou, Yuhui; Pang, Mao; Chen, Shengfeng; Xiao, Longyou; Yuan, Qiuju; Liu, Bin; Rong, Limin; He, Liumin
Abstract: The fluid‐filled cystic cavity sealed by a dense scar developed following traumatic spinal cord injury (SCI) has been a major obstacle to neural regeneration and functional recovery. Here the transected lesion is bridged using a functional self‐assembling peptide (F‐SAP) hydrogel loaded with membrane‐permeable intracellular sigma peptide (ISP) and intracellular LAR peptide (ILP), targeted at perturbing chondroitin sulfate proteoglycan (CSPG) inhibitory signaling. As compared to F‐SAP hydrogel loaded with chondroitinase ABC, the F‐SAP+ISP/ILP promotes a beneficial anti‐inflammatory response via manipulation of microglia/macrophages infiltration and assembly of extracellular matrix (ECM) molecules into fibrotic matrix rather than scarring tissues. The remodeled ECM creates a permissive environment that supports axon regrowth and the formation of synaptic connections with neurons derived from endogenous neural stem cells. The remodeled networks contribute to functional recovery, as demonstrated by improved hind limb movements and electrophysiological properties. This work proposes a unique mechanism that ECM remodeling induced by CSPG‐manipulation‐based anti‐inflammation can construct a permissive environment for neural regeneration, and shed light on the advancement of manipulation of cascading cellular and molecular events potential for endogenous repair of SCI. Abstract : Injected functional self‐assembling peptide hydrogel loaded with intracellular sigma peptide/LAR peptide might promote endogenous neural regeneration by modulating chondroitin sulfate proteoglycans (CSPGs) after spinal cord injury (SCI). Local CSPG manipulation establishes an anti‐inflammatory environment by inducing anti‐inflammatory M2 phenotype, which facilitates extracellular matrix remodeling for neuronal differentiation of endogenous neural stem cells and axon regrowth. The precise modulation of CSPGs will provide novel insights for the endogenous repair of SCI potentially.